A Novel Polymorphism in Glycoprotein IV (Replacement of Proline-90 by Serine) Predominates in Subjects with Platelet GPIV Deficiency - Kashiwagi, Hirokazu; Honda, Shigenori; Tomiyama, Yoshiaki; Mizutani, Hajime; Take, Hironori; Honda, Yumiko; Kosugi, Satoru; Kanayama, Yoshio; Kurata, Yoshiyuki; Matsuzawa, Yuji (Thrombosis and Haemostasis, 1993)
To clarify the molecular basis of the deficiency of glycoprotein IV (GPIV) of the platelet surface, we analyzed GPIV cDNA synthesized from platelet RNA of five unrelated Japanese subjects whose platelets did not express GPIV.We confirmed the presence of normal-sized GPIV mRNA in platelets from subjects with GPIV deficiency. The sequence of platelet GPIV cDNA from GPIV deficient subject showed three differences when compared with the published sequence; 1) a replacement of a 478CCT codon for proline-90 by TCT for serine, 2) a four-base insertion in the 3′-noncoding region, and 3) a substitution of A for 79C in the 5′-noncoding region. The replacement of Pro90 by Ser predominates in subjects with GPIV deficiency; that is, four out of five platelets with GPIV deficiency contained GPIV mRNA encoding GPIVSer-90, while all platelets from 17 GPIV positive subjects had GPIV mRNA encoding GPIVPro-90. The sequence of platelet GPIV cDNA which did not encode GPIVSer-90 from a subject with GPIV deficiency revealed no abnormality in the coding region. The four-base insertion in the 3′-noncoding region and the substitution of A for 79C in the 5′-noncoding region seems to be unrelated to the expression of GPIV.The substitution of Ser for Pro90 might alter the GPIV structure or impair GPIV biosynthesis, resulting in a lack of detectable GPIV. This hypothesis remains to be tested.